Characterization and emplacement modelling of gold deposition within the Franciscan complex: An example from the Los Burros mining district, California - Hughes, Jacob (Kansas State University, 2018)
The Los Burros mining district (LBMD) is located within the Lucia subterrane (Underwood et al., 1995) along the Sur- San Gregorio-San Simeon-Hosgri fault system of California’s Franciscan complex. The LBMD presented an attractive gold prospecting and mining area during the late 19th and early 20th centuries. Recent interest in the area has focused on fault-offset modelling through thermochronology (Underwood et al., 1995, Chapman et al., 2016). However, the mechanism, conditions, and timing of ore formation in the area are poorly constrained due to a lack of academic interest and documentation. This research seeks to arrive at a better understanding of gold emplacement mechanisms in the LBMD through an examination of lithologic and structural controls coupled with source fluid composition and peak P/T constraints. Sampling and mapping of lithologies and structures within the vicinity of the LBMD were conducted during the summer of 2016. Samples were collected for clay-fraction and bulk-rock mineralogy via XRD analyses, petrographic inspection and interpretation, including fluid inclusion microscopy/microthermometry as well as Raman spectroscopy. These analyses were conducted in an endeavor to constrain and explain a previously identified regional thermal anomaly within the vicinity of the LBMD with the intention of characterizing and modelling the impacts of structural controls on gold deposition. The results of this study suggest gold deposition from a gas-poor, metamorphic source-fluid with approximately 300 ppm CH₄, CO₂ density of 0.15 g/cm³, and an average salinity of 1.7 wt % NaCl equivalent. These data, along with peak P/T conditions of ~285°C and 680 bars were inferred using input from illite crystallinity data, fluid inclusion microthermometry, and the application of the Raman spectroscopy of carbonaceous material (RSCM) geothermometer used by Lahfid et al. Gold mobilization from sulfide and carbonaceous-rich sediments through polyphase deformation events led to emplacement along structural and lithologic contacts likely as a syn-orogenic event. Gold emplacement occurred during the reorientation of the regional structure by transpression.
Keywords: Gold; Raman spectroscopy; Structural geology; Mining